Pharmacokinetics and Safety of Oral Administration of Meloxicam to Foals. (20th February 2013) - Raidal, S.L.; Edwards, S.; Pippia, J.; Boston, R.; Noble, G.K.
<x xml:space="preserve">Abstract</x> Background The pharmacokinetics, efficacy, and safety of meloxicam have been evaluated in adult horses, but not foals. Physiologic differences between neonates and adults might alter drug pharmacokinetics and therapeutic index. Hypotheses The pharmacokinetics of meloxicam will be different in foals compared with adult horses, and foals could be at increased risk for adverse drug effects. Animals Twenty lightbreed foals less than 6 weeks of age at commencement of the study. Methods Single and repeated oral dose pharmacokinetics were determined for meloxicam (0.6 mg/kg) in 10 foals. The safety of the drug was further evaluated in a 2nd group of 10 foals in a randomized blinded prospective study. Results Plasma concentrations after a single oral dose of meloxicam (0.6 mg/kg) and time to maximum plasma concentration were similar to adult horses. However, drug clearance was much more rapid in foals (elimination half‐life 2.48 ± 0.25 hours). Administration of 0.6 mg/kg every 12 hours was well tolerated by foals for up to 3 weeks, with no evidence of drug accumulation in plasma. Adverse effects observed in adult horses at higher dose rates were not observed in foals given 1.8 mg/kg twice daily for 7 days. Conclusions and clinical importance Meloxicam at an oral dose rate of 0.6 mg/kg every 12 hours provided plasma concentrations likely to be therapeutic. In contrast to findings for other NSAIDs, foals appeared more resilient to the adverse effects of this drug than was observed in adult horses.